2012
DOI: 10.1007/s00604-012-0796-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemistry of hemoglobin on an ionic liquid carbon electrode modified with zinc tungstate nanorods

Abstract: We have constructed a new electrochemical biosensor by immobilization of hemoglobin (Hb) and ZnWO 4 nanorods in a thin film of chitosan (CTS) on the surface of carbon ionic liquid electrode. UV-vis and FT-IR spectra reveal that Hb remains in its native conformation in the film. The modified electrode was characterized by scanning electron microscopy, electrochemical impedance spectroscopy and cyclic voltammetry. A pair of well-defined redox peaks appears which indicates direct electron transfer from the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…The app M K value was calculated as 2.062 mmol L -1 , which was smaller than that of some previous reported values such as GR-TiO2-Hb film (3.3 mmol L -1 ), [32] Nafion/ZnWO4-Hb/CILE (5.76 mmol L -1 ) [33] and CTS/GR-LDH-Hb/CILE (8.48 mmol L -1 ). [34] The lower value of app M K indicated that HRP immobilized with NiO nanoflower retained its bioactivity and had a high biological affinity to TCA.…”
Section: Electrochemical Investigationscontrasting
confidence: 69%
“…The app M K value was calculated as 2.062 mmol L -1 , which was smaller than that of some previous reported values such as GR-TiO2-Hb film (3.3 mmol L -1 ), [32] Nafion/ZnWO4-Hb/CILE (5.76 mmol L -1 ) [33] and CTS/GR-LDH-Hb/CILE (8.48 mmol L -1 ). [34] The lower value of app M K indicated that HRP immobilized with NiO nanoflower retained its bioactivity and had a high biological affinity to TCA.…”
Section: Electrochemical Investigationscontrasting
confidence: 69%
“…So the apparent Michaelis-Menten constant (K app M ) was calculated according to the Lineweaver-Burk equation [49] with the result as 2.77 mmol/L. Compared with other kinds of Hb modified electrodes, this K app M value is lower than that of some reported values such as CTS/ZnWO 4 -Hb/CILE (5.76 mmol/L) [50] and CTS/GR-LDHHb/CILE (8.48 mmol/L) [51], so the Hb molecules in CTS/3D-GR/CILE retained excellent bioactivity with a high biological affinity to TCA.…”
Section: Electrocatalytic Behavior Of Immobilized Hbmentioning
confidence: 85%
“…21.171 (n = 26, c = 0.982). The detection limit was calculated as 0.174 mmol/L (3r), which was lower than that of the previous reported results of 0.200 mmol/L on Nafion/Mb/Co/CILE [7] and 0.613 mmol/L on CTS/ZnWO4-Hb/ CILE [39]. As the TCA concentration exceeded 119.4 mmol/L, the catalytic reduction peak currents began to level off and reached a plateau, implying a Michaelis-Menten kinetic process.…”
Section: Electrocatalytic Ability Of Nafion/mb-sa-fe 3 O 4 -Gr/cile Tmentioning
confidence: 96%